PERTUKARAN SOSIAL DAN REPRODUKSI SOLIDARITAS DALAM TRADISI NARIK WIRIT - Ismail, Ismail (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
The wrist-pulling tradition is a social exchange practice based on a reciprocal system. The research aims to analyze the mechanisms of social exchange in the wrist-pulling tradition in Punggulan village using George C. Homans' theoretical framework. This research uses a qualitative approach with an ethnographic method conducted in Punggulan Village, Air Joman District, Asahan Regency, for two months. Data was collected through participant observation, in-depth interviews with 6 informants (Mrs. Pawit, Sari Rahayu, Mrs. Ayat, and 3 other residents) selected through purposive sampling, as well as documentation. The analysis uses the Miles and Huberman model integrated with seven propositions from Homans' theory. The results of this study indicate that the traditional practice of